Application of Binary Logistic Regression Analysis on Household Welfare in Banjarmasin City - Norhidayati, Annisa; Farid, Fuad Muhajirin; Annisa, Selvi; Hamidy, Anwaril (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2023)
Household welfare refers to the conditions in which households can achieve a good standard of living and fulfill their basic needs. CIFOR states that decreasing poverty can be interpreted as increasing prosperity. Based on data on the number of poor people in South Kalimantan in 2022, Banjarmasin City has the highest number of poor people and has not yet met the poverty target contained in the South Kalimantan Regional RPJM for 2021